Analysis of the feasibility and health-economics value of simultaneous bilateral pulmonary surgery - Li, Xiaoyun; Huang, Kaili; Fan, Mingyu; Tang, Xiaojun (Frontiers in Surgery, 2025)
Background and objectiveThe increased use of chest CT for clinical diagnosis and screening has improved the detection of early-stage lung cancer and the identification of bilateral lung lesions. Despite this, consensus on the feasibility of simultaneous vs. staged bilateral surgery for patients with bilateral lesions remains elusive, necessitating further investigation. This study assessed the safety, feasibility, and health-economics value of simultaneous bilateral pulmonary surgery by comparing perioperative clinical indicators and medical costs with those of unilateral surgery and simulated staged bilateral surgery.MethodsA retrospective analysis was conducted using clinical data from 78 patients who underwent simultaneous bilateral pulmonary surgery at the Lung Cancer Center of West China Hospital of Sichuan University by the same medical team from January 2016 to October 2024. An equal number of patients who underwent unilateral surgery during the same period served as controls. Perioperative indicators were compared between these groups, and medical expenses were assessed against those of a second control group undergoing simulated staged surgery.ResultsAll surgeries in both the simultaneous group and the control group were completed successfully, with patients discharged after recovery. The average surgical duration for the 78 patients in the simultaneous group was greater than that in the control group (195.8 ± 58.8 min vs. 136.83 ± 49.1 min; P < 0.001), as was the intraoperative blood loss (143.6 ± 92.8 ml vs. 93.62 ± 63.944 ml; P = 0.009). There were no significant differences in postoperative metrics between the two groups, including average duration of ICU stay (1.15 ± 0.42 days vs. 1.09 ± 0.35 days; P = 0.423), duration of drainage tube indwelling (2.47 ± 0.86 days vs. 2.15 ± 0.88 days; P = 0.079), duration of antibiotic use (2.83 ± 1.20 days vs. 2.45 ± 0.99 days; P = 0.096) or duration of hospital stay (5.40 ± 1.50 days vs. 4.91 ± 1.47 days; P = 0.114). The major complication rates were comparable between the two groups, with no statistically significant difference (14.1% vs. 10.3%, P = 0.562). The hospitalization costs of the simultaneous group were lower than those of the staged group but higher than those of the unilateral group (68,920 ± 13,384 yuan vs. 81,030 ± 10,515 yuan vs. 48,556 ± 10,371 yuan, F = 111.920, P < 0.001).ConclusionWhen indications are appropriately adhered to, simultaneous bilateral lung surgery for patients with bilateral pulmonary lesions is both safe and feasible; it reduces medical costs, increases diagnostic and treatment efficiency, conserves medical resources, and offers significant health-economics benefits.